Transformasi Kesenian Genye Kabupaten Purwakarta - Kania Rahmatul Ulum; Endang Caturwati; Enok Wartika (PANTUN, 2021)
The focus of this study is on the transformation of Genye art as an icon of Purwakarta Regency. The study has been conducted starting from the formation of genye art to the process of changing appearances at various events, namely from 2009 to 2021 at this time. The Transformation theory of Anthony Antoniades (1990) is used to examine the process of changes occuring in genye art gradually regarding the performances in the context of its society as well as internally from the aesthetics sides. Qualitative data are collected by observation both through interviews and documents including performance photos, videos, and other visual objects. The results of the analysis show that the art of genye experienced dynamic changes from the aesthetics elements associated with music, dance, and artistic. Its existence as an icon of a region shows the community’s identity for their concern and taste for art.Keywords: genye art, transformation, icon, Purwakarta.